2015
DOI: 10.1590/0102-33062015abb0028
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity in hedgerows amidst Atlantic Forest fragments

Abstract: Hedgerows are linear structures found in agricultural landscapes that may facilitate dispersal of plants and animals and also serve as habitat. The aim of this study was to investigate the relationships among diversity and ecological traits of woody plants, hedgerow characteristics (size, age, and origin), and the structure of the surrounding Atlantic Forest landscape. Field data were collected from 14 hedgerows, and landscape metrics from 1000-m buffers surrounding hedgerows were recorded from a thematic map.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…However, woody crops contain part of the hedgerows' functional diversity (i.e., the cultivated shrubs or trees) that may explain why herbaceous crops are more positively affected in terms of biodiversity than woody crops. For instance, the cultivated shrubs and trees facilitate the establishment of non-cropped perennial plants and other species (Oliveira et al, 2015). Castro-Caro et al (2015) also reported that hedges, and ground covers to a lesser extent, efficiently increased the abundance and richness of passerine communities in olive groves, particularly of insectivorous birds.…”
Section: Hedgerows Enhanced the Farmland Habitatmentioning
confidence: 99%
“…However, woody crops contain part of the hedgerows' functional diversity (i.e., the cultivated shrubs or trees) that may explain why herbaceous crops are more positively affected in terms of biodiversity than woody crops. For instance, the cultivated shrubs and trees facilitate the establishment of non-cropped perennial plants and other species (Oliveira et al, 2015). Castro-Caro et al (2015) also reported that hedges, and ground covers to a lesser extent, efficiently increased the abundance and richness of passerine communities in olive groves, particularly of insectivorous birds.…”
Section: Hedgerows Enhanced the Farmland Habitatmentioning
confidence: 99%
“…Otro factor que influencia de manera directa el uso de las cercas por parte de la fauna y flora es la riqueza y composición florística, pues entre más variedad y número de especies arbóreas se encuentren en las cercas, más nichos se generan para hábitat de fauna nativa (Sáenz et al 2006; de Castro y van den Berg 2013). Además, si las cercas vivas están compuestas por varios estratos vegetales, albergaran un mayor número de plantas que las cercas de un solo estrato; propiciando el aumento en la conservación de flora y consecuentemente de fauna nativa asociada (Merlos et al 2005;Siles et al 2013;Oliveira et al 2015). Por ejemplo, en el estudio de Pulido-Santacruz y Renjifo (2011), demostraron que las cercas vivas que exhiban sotobosque espontaneo tienen en promedio mayor riqueza florística, pues el sotobosque ayuda a proteger las plántulas dentro de las cercas; ocasionando un mayor ofrecimiento de recursos para fauna.…”
Section: Factores Que Influencian El Uso De Las Cercas Vivas Por Part...unclassified
“…A pesar de la preeminencia de las cercas vivas en algunos paisajes tropicales, existe poca información acerca de sus roles funcionales dentro de los paisajes agrícolas, ya sea como potencial de hábitat para fauna y flora o proveedor de beneficios para los agricultores, especialmente si se compara con la abundante literatura de las zonas templadas y en especial de Europa (Harvey et al 2003;Harvey et al 2005). Si bien las cercas vivas cumplen múltiples papeles dentro de los sistemas agrícolas y proveen tanto productos como servicios a los agricultores, pueden proveer una amplia gama de beneficios, incluyendo estacas vivas para las nuevas cercas (Harvey et al 2003;Muñoz et al 2003;Harvey et al 2005; Fuentealba y Martínez-Ramos 2014), forraje (Love et al 2009;Villanueva-López et al 2010), madera (Somarriba 1995;Zahawi 2005; Tobar y Ibrahim 2010) y frutos (Fuentealba y Martínez-Ramos 2014;Levasseur et al 2004;Oliveira et al 2015). Además, la deficiente información que existe en la región tropical contrasta con la creciente información e importancia de otras formas de cobertura en los agropaisajes como fragmentos de bosque, bosques riparios y arboles aislados (Harvey et al 2004).…”
Section: Introductionunclassified
“…Corridors could also act as drift fences for winddispersed seeds by intercepting them in the matrix. If these intercepted seeds can then grow to plants that produce more seeds in the corridors, the corridors effectively decrease the distance they need to travel to colonize new patches and decrease the proportion of seeds that fall in an inhospitable matrix (Oliveira et al, 2015;Bullock and Moy, 2004).…”
Section: Introductionmentioning
confidence: 99%